Subtitling Strategies of Slang Expressions in the Fast & Furious 6 Movie Subtitle - Robingah Robingah (Jurnal Sinestesia, 2019)
Movie industry nowadays is growing more and more along with the technological advances. With the development of movies in various genres, now movies have also become a lot of research projects. There are a lot of aspects can be analyzed from movies, such as language, linguistics, intrinsic elements and translation. The focus in this study is to describe the subtitling strategies on slang expressions from the English and Bahasa Indonesia subtitles of Fast & Furious 6 movie. The method used is qualitative. To categorize the slang expressions found from the subtitle, the writer used Sumarsono’s theory. From 109 data, it is found that the biggest frequency of slang type is creativity with 66 data. Then followed by Using Existing Word, 28 data, acronym 8 data, metaphor 6 data and apocope only 1 data. There is no data for metathesis found. To analyze subtitling strategies, Gottlieb’s theory is attempted. The result found there are 8 strategies attempted from 10 strategies. The 8 strategies are expansion with 6 data, transfer with 10 data, paraphrase with 74 data, imitation with 3 data, condensation with 13 data, and 1 data for transcription, deletion, and resignation. The most subtitling strategies used for translating the English slang expression from the Fast & Furious 6 movie subtitle is paraphrase.